Comparative study between using rigid diaphragm and flexible diaphragm slabs in multi-story buildings (solid slab system) under earthquake loads - Mohammed A.Hassan (Zien Journals, 2022)
The aim of this study is to inspect the variation between the flexible floor and the rigid floor analyses for the buildings. The method of finite-element is going to be implied for analyzing the buildings with the engineering software of Autodesk Robot Structural Analysis Professional 2020, the analysis was executed for the structure that having two different diaphragm for floor, and they are flexible floor and rigid floor diaphragms. In this paper the seismic analysis for10,15 and20 stories structures with reinforced concrete that has been executed by taking two kinds of floor diaphragms. The horizontal loads include seismic and wind loads that have been applied by using Autodesk Robot Structural Analysis Professional2020 for the model of multistoried buildings along all directions for the used building, by using (ASCE 7-10 / IBC 2012 )for seismic loadings and (ASCE7-5) for wind loads. According to the result data for the modeling, current study provides a great resource of information on the horizontal displacement parameters like, drift of storey, shear of storey, moments of column, axial forces and time period
Keywords: Flat slab; story shear; Story drif; Edge beams